Development of Augmented Reality–Based Picture Cards for Descriptive Text Learning in Elementary School - Efda Hidayatul Sri; Rafidhah Hanum (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
This study aimed to develop and examine the feasibility of augmented reality (AR)–based picture cards for descriptive text learning in Indonesian language instruction at the elementary school level. The study employed a Research and Development (R&D) approach using the Alessi and Trollip model, which consists of planning, design, and development stages. Feasibility evaluation was conducted through alpha testing involving two media experts and two material experts, as well as beta testing through a limited trial with Grade III elementary school students. Data were collected using expert validation questionnaires and student response questionnaires based on a four-point Likert scale, and analyzed descriptively by converting scores into feasibility percentages. The results of media expert validation showed feasibility scores of 66.6% (feasible) and 100% (very feasible), while material expert validation yielded scores of 95.4% (very feasible) and 75% (feasible). Student responses in the beta test reached an overall score of 90.0%, categorized as very feasible, indicating positive perceptions in terms of content clarity, visual display, language, and attractiveness. These findings indicate that the developed AR-based picture cards are feasible and appropriate for use as a learning medium to support the delivery of descriptive text instruction in elementary schools. Although this study did not measure learning effectiveness, the results suggest that AR-based picture cards offer a promising alternative learning resource by providing concrete visual representations that align with descriptive text learning objectives. Future research is recommended to examine the effectiveness of this media through experimental designs and broader implementation contexts.